Inhibition of PIKFYVE kinase interferes ESCRT pathway to suppress RNA virus replication - Luo, Zhen; Liang, Yicong; Tian, Mingfu; Ruan, Zhihui; Su, Rui; Shereen, Muhammad Adnan; Yin, Jialing; Wu, Kailang; Guo, Jun; Zhang, Qiwei; Li, Yongkui; Wu, Jianguo (Journal of medical virology, 2023)
Endosomal sorting complex required for transport (ESCRT) is essential in the functional operation of endosomal transport in envelopment and budding of enveloped RNA viruses. However, in nonenveloped RNA viruses such as enteroviruses of the Picornaviridae family, the precise function of ESCRT pathway in viral replication remains elusive. Here, we initially evaluated that the ESCRT pathway is important for viral replication upon enterovirus 71 (EV71) infection. Furthermore, we discovered that YM201636, a specific inhibitor of phosphoinositide kinase, FYVE finger containing (PIKFYVE) kinase, significantly suppressed EV71 replication and virus‐induced inflammation in vitro and in vivo. Mechanistically, YM201636 inhibits PIKFYVE kinase to block the ESCRT pathway and endosomal transport, leading to the disruption of viral entry and replication complex in subcellular components and ultimately repression of intracellular RNA virus replication and virus‐induced inflammatory responses. Further studies found that YM201636 broadly represses the replication of other RNA viruses, including coxsackievirus B3 (CVB3), poliovirus 1 (PV1), echovirus 11 (E11), Zika virus (ZIKV), and vesicular stomatitis virus (VSV), rather than DNA viruses, including adenovirus 3 (ADV3) and hepatitis B virus (HBV). Our findings shed light on the mechanism underlying PIKFYVE‐modulated ESCRT pathway involved in RNA virus replication, and also provide a prospective antiviral therapy during RNA viruses infections.